Uma proposta para o ensino do conceito de matrizes em ambiente computacional - Pereira, Nilce Maria de Oliveira (2016)
This present dissertation consists to propose alternative activities to the traditional teaching of matrices concept in the high school. At first it sought to identify difficulties from the students in solving problems which matrices concept were required. Subsequently, activities were proposed from routines in which employ the Scilab software in order to solve problems. Such activities followed the Didactic Engineering as a research methodology. The usage of computer in the classroom assists students learning in innovative and pleasant ways, besides enhancing interesting and performance of the group. The activities were used in a high school third grade classroom from public school network where the researcher has been working for over twenty-five years.